Análisis de los efectos socio-económicos del subsidio de la tarifa de la dignidad en el Sector Sur del Distrito Metropolitano de Quito Parroquia Solanda. - Cruz Vaca, Erika Fernanda (2013)
By studying the rate of dignity has been demonstrated ignorance and little impact on the family budget and the monthly estimated savings is $ 1.77, while the social impact is essentially the cross-subsidy applied to subscribers who exceed the ranges consumption since this rate, they will generate an additional value of $ 3.00 on their taxes as a funding source for this measure, which is not efficient as it merely kilowatts consumed, allowing any subscriber to access the residential subsidy.